Multivariate models for estimating jackass semen production and quality. Issue 2 (3rd December 2020) - Liu, Qing; Yu, Jie; Li, Min; Zhang, Ruitao; Gao, Peng; Cong, Guanglei; Cui, Daiyong; Ji, Chuanliang; Zeng, Shenming
Abstract: The purpose of this study was to analyse the effects of season, age, gonad and accessory sex glands on semen characteristics of jackass and to construct multivariate regression models to predict semen quality. In autumn, spring and summer, semen characteristics of 30 sexually mature donkeys (1, 014 ejaculations) were analysed to investigate the effect of seasons on semen quality, and gonad and accessory sex gland parameters of 12 jackasses were measured immediately after ejaculation by ultrasonography to investigate the effect of seasons on reproductive organ size. Semen (598 ejaculates), gonad and accessory sex gland parameters of 40 jackasses aged between 3 and 7 years were analysed in autumn to investigate the effects of age and reproductive organ size on semen quality and to construct multivariate models. To verify the accuracy of the models, semen (476 ejaculates), gonad and accessory sex gland parameters of 20 jackasses were measured from March to June. Results revealed that semen, gonad and accessory sex gland parameters were not affected by season and age. Progressive motility (PM) was positively correlated with long axis of the spermatic cord (LASC) and negatively correlated with percentages of sperm abnormality (PSA). Total sperm count (TSC) was positively correlated with testis circumferences (TC) and cross‐sectional area of cauda epididymis (CSACE). TC, CSACE, LASC and PSA were included into multivariate models to predict PM, TSC and functional sperm count (FSC) in 20 jackasses (PM = 72.332 + 0.428 LASC − 0.441 PSA; TSC = −169.929 + 8.728 TC + 0.253 CSACE; FSC = −206.645 + 8.788 TC + 0.258 CSACE). The predicted and observed values corresponded well. In conclusion, the tested models can be used for predicting semen quality of donkey.